2010
DOI: 10.1111/j.1751-0813.2010.00646.x
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity, mortality and body weight gain of surgically spayed, yearling Brahman heifers

Abstract: In yearling heifers, WDOT spaying resulted in lower morbidity and short-term mortality compared with flank spaying. Both methods compromised the health and welfare of some animals for up to 4 days and body weight gains were reduced during the 6 weeks post spaying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 7 publications
2
22
1
3
Order By: Relevance
“…Spayed Brahman (Bos indicus) 2 year-old heifers showed pain-related behaviours and higher cortisol for 6 h post-procedure, and body weights and gains were significantly lower in the spayed compared with control heifers at days 21 and 42, independently of the method used, indicating comparable levels of pain and stress (McCosker et al, 2010;Petherick et al, 2011).…”
Section: Spaying (Ovariectomy)mentioning
confidence: 99%
See 1 more Smart Citation
“…Spayed Brahman (Bos indicus) 2 year-old heifers showed pain-related behaviours and higher cortisol for 6 h post-procedure, and body weights and gains were significantly lower in the spayed compared with control heifers at days 21 and 42, independently of the method used, indicating comparable levels of pain and stress (McCosker et al, 2010;Petherick et al, 2011).…”
Section: Spaying (Ovariectomy)mentioning
confidence: 99%
“…Mortality was 1.5 % and 2.5 % for the WDOT and flank method, respectively. A total of 5 % of flank wounds had not healed after 42 days (McCosker et al, 2010). Another study reported that a few animals showed discomfort through mild stiffness and straining for the first 12 h and that some walked stiffly the next day (Habermehl, 1993).…”
Section: Castrationmentioning
confidence: 99%
“…Few studies have looked at the animal health and productivity effects of surgical spaying, especially using the Willis dropped ovary technique (WDOT) since it has become commonly used. This paper assessed morbidity and mortality in yearling heifers spayed by two methods under commercial conditions in northern Australia 6 …”
Section: Production Animalsmentioning
confidence: 99%
“…This paper assessed morbidity and mortality in yearling heifers spayed by two methods under commercial conditions in northern Australia. 6 In the first study, 600 Brahman heifers were randomly allocated to physical restraint and ear-tagging only (Control); physical restraint, ovariectomy ('spay' using WDOT, plus, ear-tagging and ear-marking (WDOT); or electroimmobilisation, flank spay, ear-tagging and earmarking (Flank). Heifers were observed for approximately 6 h after spaying, then twice daily until day 4 after spaying, then once daily on days 7, 10, 21 and 42.…”
Section: Surgical Spaying In Yearling Brahman Heifersmentioning
confidence: 99%
“…Duration of mating is longest in the more extensively managed beef herds of northern Australia with continuous mating commonly practiced in these herds (Bortolussi et al 2005a) due to perceived difficulties in controlling bulls (McCosker et al 2010a). The resulting calving pattern is difficult to manage as calves are born throughout the year and those calves born late in the wet season are of insufficient weight to be weaned at musters conducted early in the year.…”
Section: Beef Cattle Management Practices Within Northern Australiamentioning
confidence: 99%